PENGARUH KOMPENSASI DAN DISIPLIN KERJA TERHADAP PRESTASI KINERJA KARYAWAN PADA PERUSAHAAN UMUM DAERAH AIR MINUM (PDAM) GUNUNG POTENG KOTA SINGKAWANG - Ayu; Hutagaluh, Oskar; Sulastri (Cross-Border Journal of Business Management, 2025)
The success of an organization is influenced by many factors, one of which is employee performance. Meanwhile, employee performance is influenced by compensation and work discipline. If compensation and work discipline experience problems, it will affect employee performance. This research aims to determine the effect of partial and simultaneous compensation and work discipline on employee performance at the Gunung Poteng Drinking Water Regional Public Company, Singkawang City. The type of data in this research is quantitative with descriptive statistical data analysis using primary data and secondary data obtained from the Gunung Poteng Regional Drinking Water Company, Singkawang City. The number of samples for this research was 59 respondents using non-probability sampling techniques with a saturated sampling method. The samples used from respondents were questionnaire answers from respondents. The data analysis methods used are instrument tests, classical assumption tests, hypothesis tests using multiple linear regression tests, t tests, and F tests and coefficient of determination. These results show that the compensation variable has a positive and significant effect on employee performance at the Gunung Poteng Regional Drinking Water Company, Singkawang City with a calculated T value> T table (6.644> 3.161) or can be seen from Sig<a (0.000<0.005). Apart from that, the work discipline variable also shows a positive and significant influence on employee performance at the Gunung Poteng Regional Drinking Water Company, Singkawang City with a calculated T value> T table (5.520>3.161) or can be seen from Sig<a (0.000<0.005). Simultaneously, Compensation and Work Discipline have a positive effect on employee performance at the Gunung Poteng Regional Drinking Water Company, Singkawang City with a calculated T value> T table (103.840>3.161) and a Sig value <a (0.000<0.005).